SAE Technical Paper Series 2003
DOI: 10.4271/2003-01-3049
|View full text |Cite
|
Sign up to set email alerts
|

Modal Parameters from a Wind Turbine Wing by Operational Modal Analysis

Abstract: Operational Modal Analysis also known as Ambient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The OMA is used for the modal identification with high precision under typical operating conditions [7]. The following are some of the main advantages of the OMA:…”
Section: Introductionmentioning
confidence: 99%
“…The OMA is used for the modal identification with high precision under typical operating conditions [7]. The following are some of the main advantages of the OMA:…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques were compared in a study and a strong correlation was observed [4]. Meller et al [5] compared FDD and SSI techniques to the traditional modal analysis for mechanical rotating machines. OMA algorithms are stochastic in nature, however mechanical applications such as rotating machineries are subject to deterministic harmonic excitations from parts of the machinery.…”
Section: Introductionmentioning
confidence: 99%
“…This method is also called feature extraction method [4]. Besides Experimental Modal Analysis (EMA), OMA is an alternative of modal analysis method which used advanced signal processing tools to determined properties of mechanical structures such as frequency, damping ratios and mode shapes by utilizing measuring response of structure without using artificial excitation [5][6][7][8].OMA is also economical and fast to conduct.Due to these advantages, OMA is widely used in many engineering applications. Operational Modal Analysis (OMA) is widely used in civil structures such as buildings [9][10][11] and bridges [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Operational Modal Analysis (OMA) is widely used in civil structures such as buildings [9][10][11] and bridges [12][13][14]. This technique also applied in mechanical [15][16][17] and aerospace engineering applications [6][7].…”
Section: Introductionmentioning
confidence: 99%